2017
DOI: 10.1038/sj.bdj.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

A study to explore if dentists' anxiety affects their clinical decision-making

Abstract: Aims 1. To develop a measure of dentists' anxiety in clinical situations; 2. To establish if dentists' anxiety in clinical situations affected their self-reported clinical decision-making; 3. To establish if occupational stress, as demonstrated by burnout, is associated with anxiety in clinical situations and clinical decision-making; and 4. To explore the relationship between decision-making style and the clinical decisions which are influenced by anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
2
36
0
2
Order By: Relevance
“…This model is described in some detail elsewhere with regards to dentistry. 19 Previous research 19 has found that self-reported anxiety in response to typical dental stressors is significantly related to hypervigilant and avoidant decisionmaking and burnout. This would suggest that reductions in the chronic stress experienced by dentists should reduce unhelpful styles of decision-making and could reduce vulnerability to burnout.…”
Section: Decision-makingmentioning
confidence: 99%
See 4 more Smart Citations
“…This model is described in some detail elsewhere with regards to dentistry. 19 Previous research 19 has found that self-reported anxiety in response to typical dental stressors is significantly related to hypervigilant and avoidant decisionmaking and burnout. This would suggest that reductions in the chronic stress experienced by dentists should reduce unhelpful styles of decision-making and could reduce vulnerability to burnout.…”
Section: Decision-makingmentioning
confidence: 99%
“…What there is suggests that stress affects performance in surgeons (in particular during highly stressful laparoscopic procedures); that experienced surgeons experience less stress and are consequently less impaired, and that stress impairs surgeons' non-technical skills such as decision-making and communication skills. A recent study 19 of primary care dentists found that an increased sense of PA and increased levels of EE and DP were related to higher levels of self-reported anxiety in clinical situations suggesting that reducing burnout improves decision-making and thus should improve patient outcomes.…”
Section: Burnoutmentioning
confidence: 99%
See 3 more Smart Citations